2015
DOI: 10.3233/ch-151932
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) grafted polylactide based copolymers for the preparation of PLA-based nanocarriers and hybrid hydrogels

Abstract: In previous works, poly(D,L-lactide-co-ɛCL-poly(ethylene glycol) (poly(D,L-La-co-αPEGɛCL) amphiphilic graft-copolymers were successfully synthesized according to a copper azide-alkyne cycloaddition (CuAAC) strategy. This paper aims at reporting on the behavior of this amphiphilic copolymer in water, which was not studied in the previous paper. Moreover, the ability of the copolymer to stabilize a PLA nanoparticles aqueous suspension is presented. For this purpose, dynamic light scattering (DLS) and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As a biodegradable domain with hydrolysis property, poly­( dl -lactide) (PLA), which is aliphatic polyester, is a widely accepted polymer and has been studied to design biodegradable materials for various applications including scaffolds for tissue regeneration and drug-delivery systems . The amphihilic block copolymers containing a PLA segment and a hydrophilic segment have been designed for construction of degradable and injectable hydrogels driven by physical cross-linking through a thermal transition responding to physiological temperature. Although the PLA domain’s feasibility has been verified, a chemical cross-linking gelation system with injectable property based on PLA cross-linker segment, which may have a great advantage on tissue regeneration as mentioned above, has not been reported yet to the best of our knowledge. PLA is inherently hydrophobic and the efficiency of the chemical reaction in aqueous milieu may limit the gelation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…As a biodegradable domain with hydrolysis property, poly­( dl -lactide) (PLA), which is aliphatic polyester, is a widely accepted polymer and has been studied to design biodegradable materials for various applications including scaffolds for tissue regeneration and drug-delivery systems . The amphihilic block copolymers containing a PLA segment and a hydrophilic segment have been designed for construction of degradable and injectable hydrogels driven by physical cross-linking through a thermal transition responding to physiological temperature. Although the PLA domain’s feasibility has been verified, a chemical cross-linking gelation system with injectable property based on PLA cross-linker segment, which may have a great advantage on tissue regeneration as mentioned above, has not been reported yet to the best of our knowledge. PLA is inherently hydrophobic and the efficiency of the chemical reaction in aqueous milieu may limit the gelation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It also supports the structure and functions of the newly formed tissue. There are certain criteria for a scaffold to provide all of the above [34,36,39,41]: it should have a proper internal structure and surface that can support cellular behaviors such as adhesion, differentiation, and proliferation [30]; it should have mechanical properties alike to the ones in the repair site [30]; and it should be biocompatible. Its properties rely on the modifications that were applied to it and the nature of the biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous epidermal stem cells obtained in culture via development of holoclones were retrovirally interacted with laminin 5 and were effectively relocated in people with junctional epidermolysis bullosa. The implants renewed a healthy epidermis at day 8, and the usual epidermis was preserved during 1 year of continuation [30].…”
Section: Transfer Techniques Therapeutic Mediator Submission Reasons mentioning
confidence: 95%
“…For instance, Riva et al reported PLA-g-PEG amphiphilic gra copolymer by copolymerizing lactide with a-chloro-3-caprolactone, through which the halogen was introduced into the backbone, followed by graing PEG onto the backbone via click chemistry. 35 However, this approach employing PLA as the backbone is not so convenient since that on one hand, it is not an easy task to incorporate functionalities such as halogen and hydroxyl into the backbone; on the other hand, because of the PLA-based backbone, many characteristics of PLA including crystallinity and mechanical properties might disappear. 36,37 It is more common to introduce PLA as side chains while preparing PLA-based gra copolymers.…”
Section: Introductionmentioning
confidence: 99%